Image quality of two different mobile cone beam computed tomographs for maxillofacial surgery - Seeberger, Robin; Seethaler, Andreas Christian; Hoffmann, Jürgen (Journal of cranio-maxillofacial surgery, 2012)
Purpose: We evaluated two mobile cone beam computed tomographs (mCBCT) comparing image quality with respect to radiation dosage. Image quality was analyzed by using different scanning modes. Materials and methods. The skulls of three human cadavers were scanned by use of conventional Computed Tomography (CT) as well as with two mobile cone beam computed tomographs (Siemens Arcadis Orbic 3D and ZiehmVision Vario 3D). Six different acquisition modes with different radiation dosages were used. The axial views of all scans were evaluated by five medical doctors regarding image quality by identifying predefined anatomical structures of the skull. A five-point ranking scale was used. The inter-rater reliability was statistically depicted by Cohen’s Kappa coefficient. A Wilcoxon signed rank test was used to evaluate the rater’s results. For evaluating the signal-to-noise ratio (SNR) a Catphan 600 reference body with two different inlays was used. Results: Comparing the mCBCTs, the image quality of the Siemens Arcadis Orbic 3D in high-dosage mode received the best score (median: 2.27). The inter-rater reliability was fair (Kappa=−0.030 to 0.328). The Wilcoxon test showed significant (p<0.05) different median rating values in 18 out of 21 imaging modes. The SNR was higher (better) in the high-dosage modes. Conclusion:Intra-operative 3D imaging by using mCBCT for maxillofacial surgery in low-dose mode acquisition is adequate in terms of signal-to-noise ratio and image quality. The image quality does not correlate in a linear manner with a higher radiation dosage. Surgeons using this technique should gather their own experience with the different acquisition modes.
Available online 21 February 2012
Gesehen am 26.06.2018